The Presentation, Assessment, Pathogenesis, and Treatment of Calcinosis in Juvenile Dermatomyositis - Hoeltzel, Mark F. (Curr Rheumatol Rep, 2014)
Calcinosis is one of the hallmark sequelae of juvenile dermatomyositis (JDM), and despite recent progress in the therapy of JDM, dystrophic calcification still occurs in approximately one-third of patients. This review discusses our current, albeit limited, understanding of risk factors for the development of calcinosis in JDM, as well as approaches to assessment, and current views on its pathogenesis. Anecdotal approaches to treating calcinosis associated with JDM, including both anti-inflammatory therapies and agents aimed at inhibiting the deposition of calcium hydroxyapatite, are reviewed. An improved understanding of the pathogenesis of calcinosis, the establishment of standardized measurement tools to assess calcinosis, and randomized controlled trials employing more sensitive outcome measures are needed to develop efficacious therapies for this often disabling complication.